The spaces of UK students' unions: extending the critical geographies of the university campus. (18th May 2016) - Brooks, Rachel; Byford, Kate; Sela, Katherine
Abstract: This article seeks to further our knowledge of the university campus by focusing on one particular aspect of most UK campuses: the students' union. UK students' unions have rarely been the subject of scholarly attention, despite them now occupying an important place within the higher education landscape. Nevertheless, in this paper we draw on a UK-wide study of students' unions to explore, firstly, the role played by the buildings of the students' union and, secondly, the ways in which aspects of the university's campus influence union activity. We pay particular attention to the expansion of the university campus, in many institutions, from a single site to multiple sites, both within the UK and overseas. We contend that a focus on the materiality of the students' union and the level of union activity (or inactivity) across various campus spaces can illustrate the values, ideologies and power relations that dominate contemporary British higher education.